Organic Field‐Effect Transistor Nonvolatile Memories with Hydroxyl‐Rich Polymer Materials as Functional Gate Dielectrics. (27th August 2019) - Xu, Ting; Zou, Jiawei; Guo, Shuxu; Qi, Weihao; Li, Shizhang; Xu, Meili; Xie, Wenfa; Cui, Zhanchen; Wang, Wei
Abstract: Organic field‐effect transistor‐ (OFET‐) based nonvolatile memories (NVMs) are becoming more important as a core component in flexible and wearable electronics. New polymer materials containing abundant hydroxyl groups are synthesized and employed as the functional gate dielectric for OFET‐NVM devices. The dependence of the memory performances on the hydroxyl content of the polymers is investigated. A variety of gate dielectric structures are proposed to verify that the memory mechanism originates from the reversible remnant polarization of hydroxyl groups in the polymers and to improve the retention capability of the OFET‐NVM devices by preventing the charge trapping in the polymers at the reading state. As a result, good memory performance is achieved with a large memory window of 33.7 V and memory on/off ratio of 1.1 × 10 4 on average, long retention properties with clearly distinguishable binary states over 10 000 s, and reliable writing/erasing switching endurance over 200 cycles in the optimal OFET‐NVM device, in which the polymer with the most hydroxyl content is sandwiched by two insulator films. Good strategies for the design of the polarizable polymers as the functional gate dielectrics and for improvement of OFET‐NVM device performance are demonstrated. Abstract : New polymers containing abundant hydroxyl groups are synthesized as the functional gate dielectrics of organic transistor nonvolatile memories. The mechanism contributing to the polarization of hydroxyl groups is confirmed. The dependence of memory performance on the hydroxyl groups content in polymers is researched. High‐performance nonvolatile memories are achieved after further optimizing the gate dielectric structure.